Cost-effectiveness study of closed system transfer devices for the preparation of antineoplastic agents - Gloria Calzado-Gómez; Gloria Julia Nazco-Casariego; Maria Micaela Viña-Romero; Fernando Gutiérrez-Nicolás (Farmacia Hospitalaria, 2017)
Most cytostatic drugs cannot be administered directly to patients in their marketed presentation, but require previous reconstitution conducted in the Pharmacy Unit areas for cytostatic preparation. There are systems that allow drug reconstitution and transfer once it has been diluted, in order to protect staff from any potential contamination during handling. These are commonly known as Closed Systems, and generally have a piece for vial attachment and a syringe adapter with a built-in filter, that replace the traditional needles. Closed systems feature different characteristics and costs which is necessary to analyze in order to determine the most efficient one